2010
DOI: 10.1021/es101711k
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient Photocatalytic Degradation of p-Nitrophenol on a Unique Cu2O/TiO2 p-n Heterojunction Network Catalyst

Abstract: p-Nitrophenol (PNP) is a difficultly decomposed organic pollutant under solar light in the absence of strong oxidants. This study shows that under artificial solar light PNP can be effectively degraded by a Cu(2)O/TiO(2) p-n junction network which is fabricated by anodizing Cu(0) particles-loaded TiO(2) nanotubes (NTs). The network is composed of p-type Cu(2)O nanowires on the top surface and Cu(2)O nanoparticles on the inner walls of the n-type TiO(2) NT arrays. The Cu(2)O/TiO(2) network shows much higher deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
197
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(200 citation statements)
references
References 20 publications
3
197
0
Order By: Relevance
“…When further functionalized with plasmonic Au or Ag nanoparticles, the optimal photocatalyst exhibited ≈16‐fold improvement for the photocatalytic reduction of CO 2 to CH 4 compared to pure ZnIn 2 S 4 . N‐type TiO 2 can also be coupled with p‐type semiconductors such as CuO or Cu 2 O to form type II p−n hereojunctions 189, 190, 191, 192. Schaak and co‐workers synthesized a CuO‐TiO 2− x N x p–n junction though the reactive template method 193.…”
Section: Photocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…When further functionalized with plasmonic Au or Ag nanoparticles, the optimal photocatalyst exhibited ≈16‐fold improvement for the photocatalytic reduction of CO 2 to CH 4 compared to pure ZnIn 2 S 4 . N‐type TiO 2 can also be coupled with p‐type semiconductors such as CuO or Cu 2 O to form type II p−n hereojunctions 189, 190, 191, 192. Schaak and co‐workers synthesized a CuO‐TiO 2− x N x p–n junction though the reactive template method 193.…”
Section: Photocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…This fundamental parameter largely reflects electron activities and is directly related to chemical, physical, and mechanical properties of materials [2][3][4][5][6][7][8]. Recent studies have shown that EWF can be used as a sensitive parameter to characterize many surface properties of biomaterials.…”
mentioning
confidence: 99%
“…Similarly, Lixia Yang and co-workers studied high e±cient photocatalytic degradation of p-nitrophenol on a unique Cu 2 O/TiO 2 p-n heterojunction network catalyst. 33 …”
Section: Introductionmentioning
confidence: 99%